2003
DOI: 10.1016/s1010-7940(03)00172-6
|View full text |Cite
|
Sign up to set email alerts
|

Does the noise of mechanical heart valve prostheses affect quality of life as measured by the SF-36® questionnaire?

Abstract: Patients (94.2%) with mechanical heart valve replacement have no persistent complaints about the valve noise. The grade of annoyance by valve noise is paralleled by lower average quality of life. Age under 60 years or being female increases the probability of severe disturbance due to mechanical valve sounds. It remains unclear whether the disturbing noise is reason or consequence of lower quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 11 publications
2
43
0
Order By: Relevance
“…In cardiac surgery, an assessment of HRQOL by means of the SF-36 questionnaire has been used in patients undergoing myocardial revascularization [16], after surgery on heart valves [17,18] or the thoracic aorta [19], and after interventions for cardiac arrhythmias [20]. It also has proven effective in patients after valve replacement with a mechanical heart valve prosthesis which when closing produces a clicking sound [21]. …”
Section: Introductionmentioning
confidence: 99%
“…In cardiac surgery, an assessment of HRQOL by means of the SF-36 questionnaire has been used in patients undergoing myocardial revascularization [16], after surgery on heart valves [17,18] or the thoracic aorta [19], and after interventions for cardiac arrhythmias [20]. It also has proven effective in patients after valve replacement with a mechanical heart valve prosthesis which when closing produces a clicking sound [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Retrospective analysis of the Veterans AffaiRs Study to Improve Anticoagulation Registry demonstrated that patients with mental health conditions had a lower time in therapeutic ratio after adjusting for other covariates [7] . Mechanical heart valves also have an audible click which has been shown to affect a patient's health-related quality of life raising the likelihood of nonadherence [8] .…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with the findings of a previous study (Koertke et al . ), which described that self‐reported quality of life was reversely correlated with the valve noise perception grade. Younger patients were more disturbed by the noise than older ones and women were more disturbed by the valve noise than men.…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1960s, heart valve surgery has evolved into a routine clinical application with a good patient outcome (Koertke et al 2003). AVR is the most common surgical valve procedure.…”
Section: Introductionmentioning
confidence: 99%